2010
DOI: 10.1007/s10900-010-9259-0
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Care and Outcomes: Disparities Across Rural America

Abstract: We examined differences in receipt of diabetes care and selected outcomes between rural and urban persons living with diabetes, using nationally representative data from the 2006 Behavioral Risk Factor Surveillance System (BRFSS). "Rural" was defined as living in a non-metropolitan county. Diabetes care variables were physician visit, HbA1c testing, foot examination, and dilated eye examination. Outcome variables were presence of foot sores and diabetic retinopathy. Analysis was limited to persons 18 and older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
95
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 25 publications
1
95
1
Order By: Relevance
“…Individuals living with T2DM in rural areas face multiple challenges, including lack of access to diabetes education [8] and clinical services [9], limited cell phone coverage and internet access [10], limited transportation and long travel distances [5], as well as higher rates of poverty [11]. These challenges in turn contribute to suboptimal diabetes management and higher rates of diabetes-related complications [9, 12•]. …”
Section: Introductionmentioning
confidence: 99%
“…Individuals living with T2DM in rural areas face multiple challenges, including lack of access to diabetes education [8] and clinical services [9], limited cell phone coverage and internet access [10], limited transportation and long travel distances [5], as well as higher rates of poverty [11]. These challenges in turn contribute to suboptimal diabetes management and higher rates of diabetes-related complications [9, 12•]. …”
Section: Introductionmentioning
confidence: 99%
“…There were positive remarks in terms of treatment adherence, metabolic control, and coping with the disease as other authors have reported [22], which translated into an improved quality of life.…”
Section: Discussionmentioning
confidence: 58%
“…This approach has proven successful encouraging patients to incorporate lifestyle changes, and even motivating participants to continue attending meetings after completing the program and despite transportation barriers [22].…”
Section: Discussionmentioning
confidence: 99%
“…Primary care physicians manage approximately 90% of diabetes clinical care in generalist clinics. The percentage is even higher in rural areas (Hale, Bennett, & Probst, 2010). Caring for diabetes in the clinic requires expertise with a foundation in biology, and outside the clinic, caring for diabetes requires separate expertise with a foundation in community 776 D. Rugh organization and social learning theory.…”
Section: Introductionmentioning
confidence: 99%
“…Often, educational classes in hospitals are the only support for rural primary care clinics. These hospital classes have high barriers of access and limited potential for behavioral change (Hale, Bennett, & Probst, 2010;Siminerio, Piatt, & Zgibar, 2005). The self-directed care program delineated in this article was developed for patients in rural communities, who receive diabetes care at primary care clinics.…”
Section: Introductionmentioning
confidence: 99%